Environmental planning, policies and programmes in India - Saksena , K. D. (New Delhi, 1993)
The book analyses the processes and problems of environmental planning, including regional planning, and the constitutional, legal, institutional and policy framework created for such planning in India. It deals with environmental problems related to land and land use, pollution and hazardous substances. The various programmes being implemented to tackle these problems, such as, the programmes for wastelands development, forest conservation, wild life protection, pollution control, management of hazardous substances, environmental education and information, en vironmental research and enviromental and for estry training, have been discussed. The book contains an analysis of the problems and programmes related to hill areas, islands, agro climatic zones, bio-sphere reserves, wetlands, mangroves and coral reefs, urban regions and coastal areas. The concepts and procedures involved in Environmental Impact Assessment too have been discussed. The book also draws several useful conclusions and makes practical suggestions based thereon.
Keywords: Environmental policies